2009
DOI: 10.1111/j.1365-2362.2009.02102.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of 5‐HT3 receptor antagonist, tropisetron on experimental colitis in rats

Abstract: Tropisetron exert beneficial effects in experimental rat colitis and therefore might be useful in the treatment of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 52 publications
(62 reference statements)
7
63
0
Order By: Relevance
“…Granisetron and tropisetron also decreased colonic content of inflammatory cytokines (30,31). The antiinflammatory effects of granisetron were canceled by concurrent administration of mCPBG (30).…”
Section: Discussionmentioning
confidence: 93%
“…Granisetron and tropisetron also decreased colonic content of inflammatory cytokines (30,31). The antiinflammatory effects of granisetron were canceled by concurrent administration of mCPBG (30).…”
Section: Discussionmentioning
confidence: 93%
“…Murine studies with tropisetron and other 5-HT 3 R as well as 5HT 4 R antagonists revealed that motility is disturbed in the duodenum after treatment with all of these drugs, with the exception of tropisetron, suggesting that its effect on the 5-HT 4 R is of minor extent (Nylander and Pihl, 2006). Another particular feature of tropisetron is its anti-inflammatory effect that has been shown in experimental colitis in the rat, for example (Mousavizadeh et al, 2009). It is not clear from the literature to which extent this effect is dependent on 5-HT 3 R blockage or on other mechanism such as modulation of the ␣7-acetylcholine receptor pathway that also mediates anti-inflammatory effects (Abdrakhmanova et al, 2010;Kohnomi et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…This drug, which is otherwise used to control radiation-and chemotherapy-induced or postoperative nausea and vomiting, might act on the intestinal, the hepatic, and the systemic level (Gan, 2005). The effects of tropisetron, which comprise not only modulatory effects on neurons but also anti-inflammatory properties, are possibly mediated not solely through 5-HT 3 R (Thompson and Lummis, 2006;Mousavizadeh et al, 2009). We focused our studies on intestinal and hepatic effects of tropisetron, and we also tested the more specific 5-HT 3 R antagonist palonosetron to find out whether or not the beneficial effects are rather related to the inhibition of the 5-HT 3 R. The studies were performed using a well established genetic model of obesity, the ob/ob mouse (Anstee and Goldin, 2006), which is characterized not only by the absence of functional leptin but also by thymic atrophy and defective immune responses concerning dendritic, regulatory, and natural killer cells (Macia et al, 2006;Ilan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Use of the 5-HT 3 receptor antagonist tropisetron is one such intervention reported to exhibit immunomodulatory effects. Anti-inflammatory effects of it have been reported in chronic inflammatory diseases such as inflammatory bowel disease and fibromyalgia [8,9], but not yet tested in sepsis.…”
Section: Introductionmentioning
confidence: 98%